ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI DIVIDEN TUNAI PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sariati Sariati; Rasyid Hs Umrie; Mu’izuddin Mu’izuddin (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2014)
This research is conducted to analyze the influence of tree cash flows, investment opportunity sets, growth, and firm sizes on the cash dividends of the companies registered in Indonesia in the period of 2007-2010. The population of this research is 443 companies registered in Indonesia in the period of 2007-2010. The sample consistes of 37 companies and is selected using a purposive smpling technique with these two criteria: (1) the companies regulary paid dividends within the period of 2007-2010, and (2) the companies issued financial statement reports within the period. The data were analyzed by multiple linear regression computations, F testing, and t testing under the reliability coefficient of 5 %. The research results show that free cash flows, investment opportunity sets, growth, and firm sizes simultaneously influence the cash dividends given by of the companies. The investment opportunity sets and firm sizes show a positive and significant influence on the cash dividends while the free cash flows and growth do not.Keyword : Free Cash Flow, Investment Opportunity Set, Growth, Firm Size and cash Dividend.